Pengaruh Latihan FITT Level Moderate untuk Motorik Kasar dan Halus pada Siswa Disabilitas Tuna Rungu di SLB Negeri Semarang - Katon Cikal Wangsa Yudha; Danang Aji Setiawan; Husnul Hadi (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aimed to examine the effect of moderate-level FITT (Frequency, Intensity, Time, and Type) training on gross and fine motor skills in students with hearing impairments. The research employed a pre-experimental design using a one-group pretest–posttest approach. The intervention program was conducted for 6–8 weeks, three times per week, at moderate intensity (50–70% of maximum heart rate). Data were analyzed using the Wilcoxon signed-rank test. The results indicated a significant improvement in gross motor skills following the training program (p < .05), suggesting that moderate-intensity FITT training effectively enhances balance and motor coordination. In contrast, fine motor skills did not show a statistically significant improvement (p > .05). These findings indicate that moderate-level FITT training is more effective in developing global motor abilities than precision-based skills. Therefore, more specific and task-oriented training programs are required to improve fine motor performance in students with hearing impairments.